Comparative genetic study of group B streptococcal strains of human and bovine origin - Dmitriev, A; Tkáciková, L; Suvorov, A; Kantíková, M; Mikula, I; Totolyan, A (Folia microbiologica, 1999)
The presence and restriction fragment length polymorphism (RFLP) of DNA fragments hybridizing with virulence and "house keeping" gene probes were analyzed for 87 group B streptococcal (GBS) strains of human and bovine origin. Most characteristics obtained for bovine strains were similar when compared with those for human strains. The most significant degree of RFLP was discovered for the sizes of HindIII fragments containing bca gene. Human GBS strains with bac gene, encoding beta antigen with IgA binding capacity, were characterized by almost identical complex hybridization patterns with multiple gene probes. At the same time bac gene was not found among bovine GBS strains. Gene scpB that encodes C5a peptidase in all human GBS strains was detected only in 9 of 39 strains of bovine origin. These two characteristics effectively distinguished bovine GBS strains from GBS strains of human origin.
Keywords: DNA bakterií; Humans; sekvence nukleotidů; DNA primery; druhová specificita; Polymorphism, Restriction Fragment Length; Genes, Bacterial; Virulence; lidé; zvířata; Streptococcus agalactiae; virulence; genetická variace; Genetic Variation; DNA, Bacterial; Cattle; Base Sequence; bakteriální geny; skot; DNA Primers; Species Specificity; Animals; polymorfismus délky restrikčních fragmentů